Method for inducing homogeneous nucleation growth of gold nanowires through shearing force
By adding specific ligands and L-ascorbic acid to the chloroaulic acid solution and generating shear force using a constant temperature oscillator, the homogeneous nucleation growth of gold nanowires was successfully induced, and the shear force induced by the shear force in the prior art was solved. The lack of research on nanowire growth has achieved efficient and low-cost gold nanowire synthesis.
Patent Information
- Application Number
- CN202310945303.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, few studies have been conducted on the induction of shear force on the growth of gold nanowires, mainly focusing on the influence of shear force on the sorting of nanowires, but we have not effectively explored how shear force promotes the nucleation and growth of nanowires.
Add octadecyltrimethylammonium bromide or cetyltrimethylammonium bromide and L-ascorbic acid mixed solution to the chloroauric acid solution, and add a gold triangle sheet with a side length of 150nm as the internal standard, and oscillate using constant temperature. The device generates shear force and regulates the reaction conditions to induce homogeneous nucleation growth of the gold nanowires.
The homogeneous nucleation growth of gold nanowires is achieved through shear force, and the twisted and uneven surface gold nanowires are produced, with an average diameter of 39nm and an average length of 14.32μm. It is simple to operate, cheap to react and easy to react. Advantages of control.
Smart Images

Figure CN119426583A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the synthesis of nano materials, in particular to a method for growing gold nanowires by homogeneous nucleation induced by shear force. Technical Background
[0002] Gold nanowires are a type of nanomaterial with a high aspect ratio. With their unique electrical properties, catalytic properties and biocompatibility, they have shown broad application prospects in the fields of biology, catalysis, conductive materials, photonics and sensors. Existing methods for synthesizing gold nanowires are mainly divided into chemical and physical methods. Compared with the physical method that requires complex and expensive instruments, the chemical method is simpler to operate, has lower costs and mild reaction conditions, and is easier to mass-produce nanostructures with more complex morphologies.
[0003] Over the past few decades, attempts have been made to promote homogeneous nucleation by adding mechanical stimulation to solutions. There are many reports that shear forces affect the rate of homogeneous nucleation in solutions, but there is no universally accepted explanation so far. The explanation that is accepted by more researchers is that nucleation is due to the interaction between three shear-mediated effects: shear-enhanced cluster growth, cluster merging, and cluster fragmentation. They found that the nucleation rate has a significant non-monotonic relationship with the shear rate. For high shear rates, the elongation caused by shear will exceed the growth rate of the clusters, resulting in shear-induced cluster fragmentation and a corresponding decrease in the homogeneous nucleation rate.
[0004] However, existing studies have only investigated the degree of aggregation of particles under shear force. Studies related to nanowires have only simply studied the effect of shear force on the ordering of nanowires. There are few studies on whether shear force can induce the growth of nanowires. Summary of the invention
[0005] The purpose of the present invention is to provide a method for growing gold nanowires by shear force-induced homogeneous nucleation. The present invention uses chloroauric acid as a raw material, octadecyltrimethylammonium bromide or hexadecyltrimethylammonium bromide, and a mixed solution of L-ascorbic acid as a reaction system, and a gold triangle sheet with a side length of 150 nm is added as an internal standard. The number change of the gold nanowires is determined by counting the number ratio of the gold triangle sheet and the gold nanowire. In this system, by changing the type of ligand, the concentration of the gold triangle sheet, the rotation speed, the reaction temperature, the concentration of chloroauric acid, the concentration of L-ascorbic acid, C 18 TAB or C 16The TAB concentration and different shear force input modes are used to realize the synthesis of gold nanowires with different yields. The method of generating shear force by oscillating a constant temperature oscillator and then growing gold nanowires has the advantages of simple operation, low cost, easy reaction control, simple process and flow, and provides a new method for the synthesis of gold nanowires. A large number of twisted and uneven gold nanowires with an average diameter of 39nm and an average length of 14.32μm can be grown in the solution.
[0006] In order to solve the technical problem of the present invention, a technical solution is proposed: a method for growing gold nanowires by homogeneous nucleation induced by shear force, comprising the following steps:
[0007] Preparation of shear-induced growth of gold nanowires, specifically weighing octadecyl trimethyl ammonium bromide (C 18 TAB) or hexadecyltrimethylammonium bromide (C 16 TAB), which was placed in deionized water and ultrasonicated until completely dispersed to obtain a clear and transparent C 18 TAB solution or C 16 TAB solution was preheated to 60°C; 20 mM chloroauric acid and 0.1 M L-ascorbic acid were placed in a 18 TAB or C 16 In the TAB aqueous solution, the final concentration of chloroauric acid is 0.049mM to 0.294mM, the final concentration of L-ascorbic acid is 0.162mM to 3.24mM, C 18 TAB or C 16 The final concentration of TAB is 0.98mM to 49mM. 0μL to 500μL of gold triangles with a side length of 150nm are quickly added to the mixture at once under vigorous vortex shaking; the mixture is placed in a constant temperature oscillator at a speed of 50rpm to 300rpm at 20℃ to 80℃ for 30min; after the reaction is completed, it is naturally cooled to room temperature, and the resulting gold nanowires are washed twice with deionized water and dispersed in deionized water.
[0008] Preferably, the volume of the triangular seed piece is 0 μL.
[0009] Preferably, the rotation speed of the constant temperature oscillator is 300 rpm.
[0010] Preferably, the temperature of the constant temperature oscillator is 60°C.
[0011] Preferably, the gold triangle sheet is used to calculate the gold wire yield.
[0012] Preferably, the final concentration of chloroauric acid is 0.049 mM.
[0013] Preferably, the final concentration of L-ascorbic acid is 3.24 mM.
[0014] Preferably, C 18 TAB or C 16 The final concentration of TAB was 10 mM.
[0015] Preferably, the length of the gold nanowire is 0.5 to 20 μm, the diameter of the wire is 25 to 80 nm, and the gold nanowire is completely induced by the shear force generated by the oscillation.
[0016] Preferably, gold particles with a diameter of 3-5 nm are prepared by weighing a certain amount of chloroauric acid and sodium citrate at concentrations of 0.274 mM and 0.274 mM, respectively, and dissolving them in 7.3 mL of deionized water, then rapidly adding 0.2 mL of 0.1 M sodium borohydride solution in an ice water bath at one time under vigorous stirring, and then stirring at a speed of 1000 rpm for 5 min to prepare gold particles with a diameter of 3-5 nm;
[0017] Preparation of a 150 nm side length gold triangle sheet, specifically: weigh a certain amount of hexadecyl trimethyl ammonium bromide (C 16 TAB), chloroauric acid, sodium hydroxide, potassium iodide, and L-ascorbic acid are dissolved in 108 mL of deionized water at concentrations of 25 mM, 0.273 mM, 0.545 mM, 0.049 mM, and 0.545 mM, respectively, and ultrasonicated until completely dispersed to obtain a clear and transparent growth solution. The obtained growth solution is then divided into three parts: A: 0.9 mL, B: 9 mL, and C: 92 mL; 0.1 mL of the gold particles described in step (1) is quickly added to the growth solution A, and the solution is immediately added to the growth solution B after gently shaking for three seconds, and then the solution B is immediately added to the growth solution C after gently shaking for three seconds, and then the solution C is allowed to stand for 48 hours, and then the purple supernatant is slowly poured out, and 10 mL of 25 mM CTAB solution is poured into the container where the green substrate is deposited. After ultrasonication, a gold triangle solution with a side length of 150 nm is obtained, which is washed three times with a 25 mM CTAB solution before use;
[0018] Weigh 0.0197 g of octadecyltrimethylammonium bromide, place it in 5 mL of deionized water and ultrasonically disperse it until it is clear and transparent, and preheat it to 60°C. Measure 12.5 μL of 20 mM chloroauric acid and 165 μL of 0.1 M L-ascorbic acid and place them in the octadecyltrimethylammonium bromide aqueous solution. Place the mixed solution in a constant temperature oscillator and react at 60°C at a speed of 300 rpm for 30 minutes. After the reaction is completed, naturally cool to room temperature. The obtained product is washed twice with deionized water and dispersed in deionized water.
[0019] Beneficial effects:
[0020] Compared with the prior art, the present invention studies the influence of shear force on the generation of gold nanowires, and synthesizes gold nanowires with different gold wire-gold triangle sheet ratios mainly by regulating the type of ligand, the concentration of gold triangle sheets, the oscillation rate of a constant temperature oscillator, the reaction temperature, the concentration of chloroauric acid, the concentration of L-ascorbic acid, the concentration of hexadecyltrimethylammonium bromide, and different shear force input methods. In addition, a gold triangle sheet with a side length of 150nm is added as an internal standard, and the number change of the gold wire is judged by counting the number ratio of the gold nanowires and the gold triangle sheets. The method of generating shear force by oscillating a constant temperature oscillator and then growing gold nanowires in the present invention has the advantages of simple operation, low cost, easy reaction control, and simple process and flow, and provides a new method for the synthesis of gold nanowires.
[0021] (1) The parameters in Example 1 are optimal, and the number of gold wires obtained is the largest among all the examples. The product was analyzed by scanning electron microscopy, and it was found that the gold nanowires were twisted and had an uneven surface, with an average diameter of 39 nm and an average length of 14.32 μm.
[0022] (2) The product was analyzed by scanning electron microscopy or transmission electron microscopy, and it was found that the longer the ligand chain, the longer and more uniform the wires, while the shorter the ligand chain, the fewer and more uneven the wires. Furthermore, when the ligand chain length is equal to or shorter than 12, no wires are generated.
[0023] When the ligand is C 16 In TAB, the average diameter of the gold wires was 69 nm, the average length was 6.48 μm, and the number ratio of the gold wires to the gold triangles was 36.93%.
[0024] When the ligand is C 18 When TAB is used, the average diameter of the gold wire is 47 nm, the average length is 16.36 μm, and the ratio of the number of gold wires to the number of gold triangles is 52.66%. 18 In TAB, the number of gold wires is the largest, they are the longest and have uniform thickness.
[0025] When CTAB was replaced with sodium bromide, there were also very small amounts of gold wires in the solution. When CTAB was replaced with CTAC, the nanosheets grew into a wrinkled sheet-like morphology, and no nanowires were found in the solution. In addition, when CTAB was replaced with hexadecyltrimethylammonium hydroxide, the reaction solution immediately changed color after chloroauric acid was added, and only very small gold particles were found in the solution without gold wires.
[0026] (3) The product was analyzed by scanning electron microscope, and it was found that when no golden triangle tablets were added to the solution, gold lines would grow and the number was larger. When excessive golden triangle tablets were added, the number of gold lines decreased significantly. When the volume of golden triangle tablets increased from 2μL to 500μL, the ratio of the number of gold lines to golden triangle tablets decreased from 173% to 4.4%. The optimal amount of golden triangle tablets added was 0μL.
[0027] (4) The product was analyzed by scanning electron microscopy, and it was found that when the system was completely static, wireless was generated in the solution; as the oscillation rate increased, the number of nanowires increased. When the speed of the constant temperature oscillator increased from 0rpm to 300rpm, the ratio of the number of gold wires to gold triangles increased from 0% to 36.93%. The optimal oscillation rate was 300rpm.
[0028] (5) The product was analyzed by scanning electron microscopy, and it was found that when the temperature was low, there were a large number of gold nanoplates in the solution, and the number of gold nanowires was small; when the temperature was too high, the number of nanowires decreased, and there were a large number of small particles. When the reaction temperature increased from 20°C to 80°C, the ratio of the number of gold wires to gold triangles first increased from 2.02% to 36.93%, and then decreased to 11.43%. The optimal reaction temperature was 60°C.
[0029] (6) The product was analyzed by scanning electron microscope, and it was found that the higher the concentration of chloroauric acid, the fewer gold wires and the more small particles. When the concentration of chloroauric acid was 0.588mM, no gold wires were produced in the solution, and instead, a large number of small particles with a diameter of about 10nm were produced. When the concentration of chloroauric acid increased from 0.049mM to 0.588mM, the ratio of the number of gold wires to gold triangles decreased from 47.65% to 0%. The optimal concentration of chloroauric acid was 0.049mM.
[0030] (7) The product was analyzed by scanning electron microscopy, and it was found that the higher the L-ascorbic acid concentration, the more gold lines and the fewer small particles. When the L-ascorbic acid concentration was 0.081mM, no gold lines were produced in the solution. When the L-ascorbic acid concentration increased from 0.081mM to 3.24mM, the ratio of the number of gold lines to gold triangles increased from 0% to 48.96%. The optimal L-ascorbic acid concentration was 3.24mM.
[0031] (8) The product was analyzed by scanning electron microscopy or transmission electron microscopy, and it was found that when the concentration of hexadecyltrimethylammonium bromide increased, the yield of gold wire in the solution increased. When the concentration of hexadecyltrimethylammonium bromide increased from 0mM to 49mM, the ratio of the number of gold wires to gold triangles increased from 0% to 52.48%. However, as the concentration of hexadecyltrimethylammonium bromide increased, the length of the gold wire decreased from 6.48μm at 9.8mM to 2.29μm at 49mM. The optimal hexadecyltrimethylammonium bromide concentration was 9.8mM. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The octadecyl trimethyl ammonium bromide (C 18 SEM photograph of gold nanowires prepared by reacting at 60°C for 30 min at a constant temperature oscillator at a speed of 300 rpm without adding gold triangle sheets.
[0033] Figure 2 The ligand added in the invention is (a) trimethylpropylammonium bromide (C 3 TAB) (b) Hexyltrimethylammonium bromide (C 6 TAB) (c) Lauryl trimethyl ammonium bromide (C 12 TAB)(d) Myristyl trimethyl ammonium bromide (C 14 TAB) (e) hexadecyltrimethylammonium bromide (C 16 TAB) (f) Octadecyltrimethylammonium bromide (C 18 SEM image of gold nanowires prepared by reacting TAB (g) hexadecyltrimethylammonium hydroxide (CTAOH) (h) ammonium bromide (i) hexadecyltrimethylammonium chloride (CTAC) at 60°C in a constant temperature oscillator at 300 rpm for 30 min.
[0034] Figure 3 SEM photos of gold nanowires prepared by adding (a) 0 μL (b) 10 μL (c) 100 μL (d) 500 μL gold triangle flakes (the total volume of the solution remains unchanged) at 60°C in a constant temperature oscillator at 300 rpm for 30 min, and (e) a curve showing the change in the ratio of gold wires to triangle flakes as the number of gold triangle flakes increases.
[0035] Figure 4 SEM images of gold nanowires prepared in the invention at 60°C for 30 min in a constant temperature oscillator at (a) 0 rpm (b) 50 rpm (c) 100 rpm (d) 150 rpm (e) 200 rpm, and (f) a curve showing the ratio of gold wires to triangles as the number of gold triangles increases.
[0036] Figure 5 SEM images of gold nanowires prepared in the present invention by reacting at (a) 20°C, (b) 40°C, and (c) 80°C in a constant temperature oscillator at 300 rpm for 30 min, and (d) a bar graph and curve showing the change in the ratio of gold wires / small particles to triangles as the number of gold triangles increases.
[0037] Figure 6 SEM photos of gold nanowires prepared by reacting at a constant temperature oscillator at a speed of 300 rpm at 60°C for 30 min when the concentration of chloroauric acid in the invention is (a) 0.049 mM (b) 0.098 mM (c) 0.196 mM (d) 0.294 mM (e) 0.588 mM, and (f) a bar graph and curve showing the change in the ratio of gold wires / small particles to triangles as the number of gold triangles increases.
[0038] Figure 7SEM images of gold nanowires prepared by reacting at 60°C for 30 min at a constant temperature oscillator at a speed of 300 rpm when the concentration of L-ascorbic acid in the invention is (a) 0.081 mM (b) 0.162 mM (c) 0.648 mM (d) 1.296 mM (e) 3.24 mM, and (f) a bar graph and curve showing the change in the ratio of gold wires / small particles to triangles as the number of gold triangles increases.
[0039] Figure 8 The concentration of hexadecyltrimethylammonium bromide in the invention is (a) 0mM (b) 0.98mM (c) 4.9mM (d)
[0040] (e) SEM image of gold nanowires prepared by reacting at 60°C for 30 min at 300 rpm in a constant temperature oscillator at 49 mM, and (e) a bar graph and curve of the change in the ratio of gold wires / small particles to triangles as the number of gold triangles increases.
[0041] Fig. 9 The SEM photograph of the gold nanowires and gold triangles prepared by stirring at 60° C. at a speed of 1000 rpm for 30 min in a water bath in the present invention using magnetic stirring as the shear force input method. DETAILED DESCRIPTION
[0042] The present invention will be further described below in conjunction with specific implementations and accompanying drawings.
[0043] Example 1
[0044] (1) Preparation of gold particles with a diameter of 3-5 nm, specifically: weigh a certain amount of chloroauric acid and sodium citrate at a concentration of 0.274 mM and 0.274 mM, respectively, and dissolve them in 7.3 mL of deionized water. Then, under vigorous stirring, quickly add 0.2 mL of 0.1 M sodium borohydride solution in an ice water bath at one time, and then stir at a speed of 1000 rpm for 5 min to prepare gold particles with a diameter of 3-5 nm.
[0045] (2) Preparation of a gold triangle sheet with a side length of 150 nm, specifically: weigh a certain amount of hexadecyltrimethylammonium bromide (C 16TAB), chloroauric acid, sodium hydroxide, potassium iodide, and L-ascorbic acid are dissolved in 108 mL of deionized water at concentrations of 25 mM, 0.273 mM, 0.545 mM, 0.049 mM, and 0.545 mM, respectively, and ultrasonicated until completely dispersed to obtain a clear and transparent growth solution. The obtained growth solution is then divided into three parts: A: 0.9 mL, B: 9 mL, and C: 92 mL; 0.1 mL of the gold particles described in step (1) is quickly added to the growth solution A, and gently shaken for three seconds and immediately added to the growth solution B, and then B is gently shaken for three seconds and immediately added to the growth solution C, and then C is gently shaken for three seconds and allowed to stand for 48 hours, then the purple supernatant is slowly poured out, and 10 mL of 25 mM CTAB solution is poured into the container where the green substrate is deposited. After ultrasonication, a gold triangle solution with a side length of 150 nm is obtained, which is washed three times with a 25 mM CTAB solution before use.
[0046] (3) Weigh 0.0197 g of octadecyltrimethylammonium bromide, place it in 5 mL of deionized water and ultrasonically disperse it until it is clear and transparent, and preheat it to 60° C. Measure 12.5 μL of 20 mM chloroauric acid and 165 μL of 0.1 M L-ascorbic acid and place them in the octadecyltrimethylammonium bromide aqueous solution. Place the mixture in a constant temperature oscillator at 300 rpm at 60° C. for 30 min. After the reaction is completed, naturally cool to room temperature. The obtained product is washed twice with deionized water and dispersed in deionized water.
[0047] like Figure 1 , the ligand is octadecyl trimethyl ammonium bromide, the final concentration of octadecyl trimethyl ammonium bromide is 10mM, the final concentration of chloroauric acid is 0.049mM, the final concentration of L-ascorbic acid is 3.24mM, no gold triangle is added, and the SEM photo of the prepared gold nanowires is placed in a constant temperature oscillator at a speed of 300rpm at 60°C for 30min. The product was analyzed by scanning electron microscopy and found that the gold nanowires were twisted and the surface was uneven, with an average diameter of 39nm and an average length of 14.32μm. The number of gold wires obtained in this embodiment is the largest among all embodiments.
[0048] Example 2
[0049] Weigh different types of ligands, place them in 5 mL of deionized water and ultrasonically disperse them until clear and transparent, so that the concentration of all ligands is 10 mM, and preheat to 60°C, measure 37.5 μL of 20 mM chloroauric acid and 16.5 μL of 0.1 M L-ascorbic acid and place them in the above aqueous solution, and then add 40 μL of 150 nm gold triangle pieces under vigorous VORTEX shaking, place the mixed solution in a constant temperature oscillator and react at 60°C for 30 min at a speed of 300 rpm. After the reaction is completed, naturally cool to room temperature, wash the product twice with deionized water and disperse it in deionized water.
[0050] like Figure 2 , the ligand added is (a) trimethylpropylammonium bromide (C 3 TAB) (b) Hexyltrimethylammonium bromide (C 6 TAB) (c) Lauryl trimethyl ammonium bromide (C 12 TAB)(d) Myristyl trimethyl ammonium bromide (C 14 TAB) (e) hexadecyltrimethylammonium bromide (C 16 TAB) (f) Octadecyltrimethylammonium bromide (C 18 SEM images of gold nanowires and gold triangles prepared with TAB (g) hexadecyltrimethylammonium hydroxide (CTAOH) (h) ammonium bromide (i) hexadecyltrimethylammonium chloride (CTAC).
[0051] The product was analyzed by scanning electron microscopy or transmission electron microscopy, and it was found that the longer the ligand chain, the longer and more uniform the wires, the shorter the ligand chain, the fewer the wires and the thickness is uneven, and when the ligand chain length is equal to or shorter than 12, no wires are produced.
[0052] When the ligand is C 16 In TAB, the average diameter of the gold wires was 69 nm, the average length was 6.48 μm, and the number ratio of the gold wires to the gold triangles was 36.93%.
[0053] When the ligand is C 18 When TAB is used, the average diameter of the gold wire is 47 nm, the average length is 16.36 μm, and the ratio of the number of gold wires to the number of gold triangles is 52.66%. 18 In TAB, the number of gold wires is the largest, they are the longest and have uniform thickness.
[0054] When CTAB was replaced with sodium bromide, there were also very small amounts of gold wires in the solution. When CTAB was replaced with CTAC, the nanosheets grew into a wrinkled sheet-like morphology, and no nanowires were found in the solution. In addition, when CTAB was replaced with hexadecyltrimethylammonium hydroxide, the reaction solution immediately changed color after chloroauric acid was added, and only very small gold particles were found in the solution without gold wires.
[0055] Example 3
[0056] Weigh 0.0182g of hexadecyltrimethylammonium bromide, place it in 5mL of deionized water and ultrasonically disperse it until it is clear and transparent, and preheat it to 60°C. Measure 37.5μL of 20mM chloroauric acid and 16.5μL of 0.1M L-ascorbic acid and place them in the hexadecyltrimethylammonium bromide aqueous solution. Then, add different amounts of 150nm gold triangle pieces under vigorous VORTEX shaking (the total volume remains unchanged), place the mixed solution in a constant temperature oscillator at 300rpm at 60°C for 30min, and naturally cool to room temperature after the reaction is completed. The obtained product is washed twice with deionized water and dispersed in deionized water.
[0057] like Figure 3 , are SEM photos of gold nanowires and gold triangle flakes prepared when the amount of gold triangle flakes added is (a) 0μL (b) 10μL (c) 100μL (d) 500μL, and (e) the curve of the change in the ratio of gold wires to triangle flakes as the amount of gold triangle flakes increases.
[0058] The product was analyzed by scanning electron microscope, and it was found that when no golden triangle flakes were added to the solution, gold lines would grow and the number was larger. When excessive golden triangle flakes were added, the number of gold lines decreased significantly. When the volume of golden triangle flakes increased from 2μL to 500μL, the ratio of gold lines to golden triangle flakes decreased from 173% to 4.4%.
[0059] The optimal amount of gold triangle flakes added is 0 μL. The triangle flakes are used as internal standards, and the gold wire yield is determined by counting the ratio of gold wire to gold triangle flakes.
[0060] Example 4
[0061] Weigh 0.0182g of hexadecyltrimethylammonium bromide, place it in 5mL of deionized water and ultrasonically disperse it until it is clear and transparent, and preheat it to 60°C. Measure 37.5μL of 20mM chloroauric acid and 16.5μL of 0.1M L-ascorbic acid and place them in the hexadecyltrimethylammonium bromide aqueous solution, then add 40μL of 150nm gold triangle pieces under vigorous VORTEX shaking, place the mixed solution in a constant temperature oscillator and react at 60°C for 30min at different speeds. After the reaction is completed, naturally cool to room temperature. The obtained product is washed twice with deionized water and dispersed in deionized water.
[0062] like Figure 4 , are SEM photos of gold nanowires and gold triangles prepared when the constant temperature oscillator speed is (a) 0rpm (b) 50rpm (c) 100rpm (d) 150rpm (e) 200rpm, and (f) the curve of the change in the ratio of gold wires to triangles as the oscillation rate of the constant temperature oscillator increases.
[0063] The product was analyzed by scanning electron microscope, and it was found that when the system was completely static, wireless was generated in the solution; as the oscillation rate increased, the number of nanowires increased. When the speed of the constant temperature oscillator increased from 0rpm to 300rpm, the ratio of the number of gold wires to gold triangles increased from 0% to 36.93%. The optimal oscillation rate was 300rpm.
[0064] Example 5
[0065] Weigh 0.0182g of hexadecyltrimethylammonium bromide, place it in 5mL of deionized water and ultrasonically disperse it until it is clear and transparent, and preheat it to the corresponding temperature. Measure 37.5μL of 20mM chloroauric acid and 16.5μL of 0.1M L-ascorbic acid and place them in the hexadecyltrimethylammonium bromide aqueous solution, and then add 40μL of 150nm gold triangle pieces under vigorous VORTEX shaking. Place the mixed solution in a constant temperature oscillator and react at different temperatures for 30min at a speed of 300rpm. After the reaction is completed, naturally cool to room temperature. The obtained product is washed twice with deionized water and dispersed in deionized water.
[0066] like Figure 5 , are SEM photos of gold nanowires and gold triangles prepared at reaction temperatures of (a) 20°C (b) 40°C (c) 80°C, and (d) a bar graph and curve showing the change in the ratio of gold wires / small particles to triangles as the reaction temperature increases.
[0067] The product was analyzed by scanning electron microscope, and it was found that when the temperature was low, there were a large number of gold nanoplates in the solution, and the number of gold nanowires was small; when the temperature was too high, the number of nanowires decreased, and there were a large number of small particles. When the reaction temperature increased from 20°C to 80°C, the ratio of gold wires to gold triangles first increased from 2.02% to 36.93%, and then decreased to 11.43%. The optimal reaction temperature is 60°C.
[0068] Example 6
[0069] Weigh 0.0182g of hexadecyltrimethylammonium bromide, place it in 5mL of deionized water and ultrasonically disperse it until it is clear and transparent, and preheat it to 60°C. Measure 37.5μL of chloroauric acid of different concentrations and 16.5μL of 0.1M L-ascorbic acid and place them in an aqueous solution of hexadecyltrimethylammonium bromide. Then, add 40μL of 150nm gold triangle pieces under vigorous VORTEX shaking. Place the mixture in a constant temperature oscillator and react at different temperatures for 30min at a speed of 300rpm. After the reaction is completed, naturally cool to room temperature. The obtained product is washed twice with deionized water and dispersed in deionized water.
[0070] like Figure 6, SEM photos of gold nanowires and gold triangles prepared when the final concentration of chloroauric acid in the system is (a) 0.049mM (b) 0.098mM (c) 0.196mM (d) 0.294mM (e) 0.588mM, and (f) a bar graph and curve showing the change in the ratio of gold wires / small particles to triangles as the concentration of chloroauric acid increases. The product was analyzed by scanning electron microscopy and it was found that the higher the concentration of chloroauric acid, the fewer gold wires and the more small particles. When the concentration of chloroauric acid was 0.588mM, no gold wires were produced in the solution, and instead, a large number of small particles with a diameter of about 10nm were produced. When the concentration of chloroauric acid increased from 0.049mM to 0.588mM, the ratio of gold wires to gold triangles decreased from 47.65% to 0%. The optimal concentration of chloroauric acid is 0.049mM.
[0071] Example 7
[0072] Weigh 0.0182g of hexadecyltrimethylammonium bromide, place it in 5mL of deionized water and ultrasonically disperse it until it is clear and transparent, and preheat it to 60°C. Measure 37.5μL of 20mM chloroauric acid and 16.5μL of L-ascorbic acid of different concentrations and place them in the hexadecyltrimethylammonium bromide aqueous solution, then add 40μL of 150nm gold triangle pieces under vigorous VORTEX shaking, place the mixed solution in a constant temperature oscillator at a speed of 300rpm and react at different temperatures for 30min. After the reaction is completed, naturally cool to room temperature. The obtained product is washed twice with deionized water and dispersed in deionized water.
[0073] like Figure 7 , SEM photos of gold nanowires and gold triangles prepared when the final concentration of L-ascorbic acid in the system is (a) 0.081mM (b) 0.162mM (c) 0.648mM (d) 1.296mM (e) 3.24mM, and (f) a bar graph and curve showing the change in the ratio of the number of gold wires / small particles to triangles as the concentration of L-ascorbic acid increases. The product was analyzed by scanning electron microscopy, and it was found that the higher the concentration of L-ascorbic acid, the more gold wires and the fewer small particles. When the concentration of L-ascorbic acid was 0.081mM, no gold wires were produced in the solution. When the concentration of L-ascorbic acid increased from 0.081mM to 3.24mM, the ratio of the number of gold wires to gold triangles increased from 0% to 48.96%. The optimal concentration of L-ascorbic acid is 3.24mM.
[0074] Example 8
[0075] Weigh different amounts of hexadecyltrimethylammonium bromide, place it in 5 mL of deionized water and ultrasonically disperse it until it is clear and transparent, and preheat it to 60°C. 37.5 μL of 20 mM chloroauric acid and 16.5 μL of 0.1 M L-ascorbic acid are placed in an aqueous solution of hexadecyltrimethylammonium bromide, and then 40 μL of 150 nm gold triangle pieces are added under vigorous VORTEX shaking. The mixture is placed in a constant temperature oscillator and reacted at different temperatures for 30 min at a speed of 300 rpm. After the reaction is completed, it is naturally cooled to room temperature. The product is washed twice with deionized water and dispersed in deionized water.
[0076] like Figure 8 , SEM photos of gold nanowires and gold triangles prepared when the final concentration of hexadecyltrimethylammonium bromide in the system is (a) 0mM (b) 0.98mM (c) 4.9mM (d) 49mM, and (e) a bar graph and curve showing the change in the ratio of the number of gold wires / small particles to triangles as the concentration of hexadecyltrimethylammonium bromide increases. The product was analyzed by scanning electron microscopy or transmission electron microscopy, and it was found that when the concentration of hexadecyltrimethylammonium bromide increased, the yield of gold wires in the solution increased. When the concentration of hexadecyltrimethylammonium bromide increased from 0mM to 49mM, the ratio of the number of gold wires to gold triangles increased from 0% to 52.48%. However, as the concentration of hexadecyltrimethylammonium bromide increased, the average length of the gold wire decreased from 6.48μm at 9.8mM to 2.29μm at 49mM. The optimal hexadecyltrimethylammonium bromide concentration is 9.8mM.
[0077] Example 9
[0078] Weigh different amounts of hexadecyltrimethylammonium bromide, place it in 5 mL of deionized water and ultrasonically disperse it until it is clear and transparent, and preheat it to 60°C. Measure 37.5 μL of 20 mM chloroauric acid and 16.5 μL of 0.1 M L-ascorbic acid and place them in an aqueous solution of hexadecyltrimethylammonium bromide. Then, add 40 μL of 150 nm gold triangle flakes under vigorous VORTEX shaking. Place the mixture in a water bath with magnetic stirring and stir at 60°C at a speed of 1000 rpm for 30 min. After the reaction is completed, naturally cool to room temperature. The product is washed twice with deionized water and dispersed in deionized water.
[0079] like Fig. 9, which is a SEM photo of gold nanowires and gold triangles prepared when the system was stirred at 1000 rpm for 30 minutes at 60°C in a water bath with magnetic stirring. The product was analyzed by scanning electron microscopy and found that when the shear force input method was changed to magnetic stirring, gold wires were still produced in the solution, but the gold wire yield was reduced to 13.9%, and the average length of the gold wire was reduced to 3.27μm, and the diameter was not as uniform as the gold wire produced under the constant temperature oscillator conditions. The best shear force input method is constant temperature oscillator oscillation.
Claims
1. A method for growing gold nanowires by homogeneous nucleation induced by shear force, characterized in that: The steps include: Preparation of shear-induced growth of gold nanowires, specifically weighing octadecyl trimethyl ammonium bromide (C 18 TAB) or hexadecyltrimethylammonium bromide (C 16 TAB), which was placed in deionized water and ultrasonicated until completely dispersed to obtain a clear and transparent C 18 TAB solution or C 16 TAB solution was preheated to 60°C; 20 mM chloroauric acid and 0.1 M L-ascorbic acid were placed in a 18 TAB or C 16 In the TAB aqueous solution, the final concentration of chloroauric acid is 0.049mM to 0.294mM, the final concentration of L-ascorbic acid is 0.162mM to 3.24mM, C 18 TAB or C 16 The final concentration of TAB is 0.98mM~49mM. 0μL~500μL of gold triangle pieces with a side length of 150nm are quickly added to the mixed solution at one time under vigorous VORTEX shaking; the mixed solution is placed in a constant temperature oscillator and reacted at a speed of 50rpm~300rpm at 20℃~80℃ for 30min; after the reaction is completed, it is naturally cooled to room temperature, and the resulting gold nanowires are washed twice with deionized water and dispersed in deionized water.
2. The method for growing gold nanowires by shear force-induced homogeneous nucleation according to claim 1, characterized in that: The volume of the triangular piece seed is 0 μL.
3. The method for growing gold nanowires by shear force-induced homogeneous nucleation according to claim 1, characterized in that: The rotation speed of the constant temperature oscillator was 300 rpm.
4. The method for growing gold nanowires by shear force induced homogeneous nucleation according to claim 1, characterized in that: The temperature of the thermostatic oscillator was 60°C.
5. The method for growing gold nanowires by shear force induced homogeneous nucleation according to claim 1, characterized in that: The gold triangle sheet is used to calculate the gold wire yield.
6. The method for growing gold nanowires by shear force induced homogeneous nucleation according to claim 1, characterized in that: The final concentration of chloroauric acid was 0.049 mM.
7. The method for growing gold nanowires by shear force induced homogeneous nucleation according to claim 1, characterized in that: The final concentration of L-ascorbic acid was 3.24 mM.
8. The method for growing gold nanowires by shear force-induced homogeneous nucleation according to claim 1, characterized in that: C 18 TAB or C 16 The final concentration of TAB was 10 mM.
9. The method for growing gold nanowires by shear force-induced homogeneous nucleation according to claim 1, characterized in that: The length of the gold nanowire is 0.5 to 20 μm, the diameter of the wire is 25 to 80 nm, and the gold nanowire is completely induced by the shear force generated by oscillation.
10. The method for growing gold nanowires by shear force-induced homogeneous nucleation according to claim 1, characterized in that: The following steps are involved: (1) preparing gold particles with a diameter of 3-5 nm, specifically: weighing a certain amount of chloroauric acid and sodium citrate at a concentration of 0.274 mM and 0.274 mM respectively, dissolving in 7.3 mL of deionized water, then rapidly adding 0.2 mL of 0.1 M sodium borohydride solution in an ice water bath at one time under vigorous stirring, and then stirring at a speed of 1000 rpm for 5 min to prepare gold particles with a diameter of 3-5 nm; (2) Preparation of a gold triangle sheet with a side length of 150 nm, specifically: weigh a certain amount of hexadecyltrimethylammonium bromide (C 16 TAB), chloroauric acid, sodium hydroxide, potassium iodide, and L-ascorbic acid are dissolved in 108 mL of deionized water at concentrations of 25 mM, 0.273 mM, 0.545 mM, 0.049 mM, and 0.545 mM, respectively, and ultrasonicated until completely dispersed to obtain a clear and transparent growth solution. The obtained growth solution is then divided into three parts: A: 0.9 mL, B: 9 mL, and C: 92 mL; 0.1 mL of the gold particles described in step (1) is quickly added to the growth solution A, and the solution is immediately added to the growth solution B after gently shaking for three seconds, and then the solution B is immediately added to the growth solution C after gently shaking for three seconds, and then the solution C is allowed to stand for 48 hours, and then the purple supernatant is slowly poured out, and 10 mL of 25 mM CTAB solution is poured into the container where the green substrate is deposited. After ultrasonication, a gold triangle solution with a side length of 150 nm is obtained, which is washed three times with a 25 mM CTAB solution before use; (3) Weigh 0.0197 g of octadecyltrimethylammonium bromide, place it in 5 mL of deionized water and ultrasonically disperse it until it is clear and transparent, and preheat it to 60° C. Measure 12.5 μL of 20 mM chloroauric acid and 165 μL of 0.1 M L-ascorbic acid and place them in the octadecyltrimethylammonium bromide aqueous solution. Place the mixture in a constant temperature oscillator at 300 rpm at 60° C. for 30 min. After the reaction is completed, naturally cool to room temperature. The obtained product is washed twice with deionized water and dispersed in deionized water.